Belonging, Defined: A Delphi Consensus on What Matters in Higher Education - Armstrong-McDowell, Clara; Priesltey, Michael; Naela, Hina; Ma, Jiachen; Li, Chengyang; Chaaban, Mya; Wu, Siyu; Chen, Siyuan; Byrom, Nicola (Journal of University Teaching and Learning Practice, 2026)
Belonging is increasingly positioned as central to student success, retention, equity, and mental health in higher education policy and practice. Yet the construct remains conceptually fragmented, with hundreds of different measures in use and limited agreement about what belonging fundamentally comprises. This lack of clarity constrains evaluation, comparison across studies, and institutional action. We conducted a three-round Delphi study to identify core components of belonging in higher education. Drawing on published definitions identified in a prior systematic review, an international panel of students and sector experts iteratively prioritised and refined descriptors. Twelve descriptors reached consensus, including being accepted, included, connected, valued, respected, safe, cared about, and feeling that one matters. These were organised into five interpretative domains: recognition and inclusion; community connectedness; ease and security; perceived care and support; and relational cohesion. This new consensus-derived framework provides a clearer conceptual foundation to guide measurement development and selection, as well as the design and evaluation of belonging-focused initiatives. In doing so, this framework can help researchers and policymakers identify and evaluate effective approaches to developing student belonging in practice.